The use of educational games as a didactic resource to motivate english learning - Chaluisa Ante, Nancy Ofelia (2016)
This research project addressed the demotivation problem in the students toward English language learning because teachers do not use appropriated didactic resource to make English classes funnier. The main aim of this research is to implement the use of educational games as an effective didactic resource in order to motivate English study as a foreign language. The research methodology used was a qualitative method where the data extracted were from three sources such as surveys that were guided to 93 Students at “INES COBO DONOSO” Educational Unit, the researcher’s observation and the interview applied to the English teacher area. By applying qualitative research method, the major findings demonstrated clearly, that is feasible to implement educational games into English language classes in order to motivate the student’s learning and develop learners’ skills. For this reason, to apply the educational games to make English classes funnier was so important because the outcome of application into English classes showed that using educational games increase students' skills and motivate toward English language learning.